Direct and Efficient (Carbonyl)cobalt‐Mediated Aryl Acetylation Using [11C]Methyl Iodide. Issue 16 (23rd May 2016) - Dahl, Kenneth; Schou, Magnus; Halldin, Christer
Abstract : A new strategy is reported that allows direct access to 11 C‐labelled aryl methyl ketones by a fast and efficient (carbonyl)cobalt‐mediated protocol employing [ 11 C]methyl iodide as the labelling agent. The method uses Co2 CO8 as combined aryl halide activator and carbon monoxide source for the carbonylation reaction. The suitability of the methodology was demonstrated by the 11 C‐labelling of a set of functionalised arenes and heteroarenes with radiochemical conversions (RCC) ranging from 22 % to 63 %. Abstract : A new strategy is reported that allows direct access to 11 C‐labelled aryl methyl ketones via a fast and efficient cobalt carbonyl‐mediated protocol using (hetero)aryl halides as substrate. RCC = radiochemical conversion.